Towards the design of an agile enterprise architecture management method - Lumor, Truth (2016)
Enterprises engage in dynamic environments and do need capabilities that will enable them to (re)configure and integrate existing capabilities or create new capabilities in order to remain viable and competitive in such environments. Enterprise Architecture (EA) by definition has the propensity to contribute to the agility of the enterprise in turbulent environments provided it is managed and guided by a methodic approach in a way that strengthens the capabilities with which the enterprise senses and responds to changes in its environment. However, the agility of the Enterprise Architecture Management (EAM) func-tion and its relation with the agility of the enterprise as a whole has been spar-ingly studies in the EA literature. This thesis contributes to the EA literature by designing an agile EAM method that supports the agility of the EAM function and the agility of the enterprise as a whole. A number of steps were taken to this end. First, the factors that influence the agility of the enterprise, namely; agility drivers, agility providers and agility capabilities, were identified. Second, litera-ture on enterprise architecture, lean and agile principles and values, and a set of proposed theories were reviewed to form the theoretical foundation for the method design effort. Third, the lean and agile principles and values were adapted for EAM work. Fourth, the adapted lean and agile principles and values were consolidated into eight essential elements (EEs) that an agile EAM should possess in order to support the agility of the EAM function and the agility of the enterprise. Finally, an agile EAM method (Agile EAMM) was constructed to embody the EEs. The proposed Agile EAMM acts as a dynamic capability that provides the sensing capabilities, the leaning capabilities and the coordinating capabilities needed to effectively carry out enterprise architecting as an integrat-ing capability in transforming as-is architecture (existing operational capabili-ties) into to-be architecture (reconfigured operational capabilities). The compat-ibility of the Agile EAMM with existing methods was demonstrated using TO-GAF’s ADM, and its efficacy was evaluated by means of an illustrative scenario. Conceptually, the Agile EAMM has the propensity to support the agility of the EAM function and the agility of the enterprise as a whole. Aside the Agile EAMM, the thesis contributes lean and agile principles and values applicable to EAM, the eight EEs, and areas for further research to the EA literature.